Pediatric gastric perforation beyond neonatal period: 8-year experience with 20 patients - Kai Wang; Siyu Cai; Lejian He; Chunhui Peng; Wenbo Pang; Zengmeng Wang; Dongyang Wu; Yajun Chen (Elsevier, 2019)
Background: To describe the characteristics, treatments, and prognosis of pediatric gastric perforation patients beyond neonatal period. Methods: Twenty pediatric patients beyond neonatal period were included in this study. Medical records were reviewed and clinical characteristics were analyzed. According to the outcomes, patients were divided into the survival group and the death group. Death time was documented, and survival patients were followed up. The degree of severity was calculated using pediatric critical illness score (PCIS). Differences between the two groups were analyzed by the Student's t-test, Mann-Whitney test and Chi-square test appropriately. Results: Gastric perforation was diagnosed in 20 pediatric patients beyond neonatal period, including 6 males (30%) and 14 females (70%), with the age of 37.18 (15.90, 107.12) months, and the range was from 4.30 months to 14.17 years old. They had different manifestations, etiologies, sites of perforation and surgery procedures. Among the 20 cases, 14 (70%) survived and 6 (30%) died. Age, gender, length and number of perforation had no statistically difference between the two groups. However, PCIS, ischemia of gastrointestinal wall, and transmural necrosis of gastric wall were statistically different. For the survival group, during a follow-up period of 50 (36, 68) months, ranging from 2 months to 8 years and 7 months, one patient had a second-time perforation, another 3 patients had brain injury symptoms, and the rest 10 patients had good quality of lives. Conclusions: Gastric perforation of pediatric patients beyond neonatal period causes a mortality of 30% on this study. Spontaneous great curvature of gastric wall perforation has the highest morbidity. Low PCIS predicts for unfavorable prognosis. Most of the survival patients have satisfactory living quality after operation. Key Words: pediatric gastric perforation, prognosis, treatment